One step synthesis of D-A-D chromophores as active materials for organic solar cells by basic condensation. (February 2015) - Jeux, Victorien; Segut, Olivier; Demeter, Dora; Rousseau, Théodulf; Allain, Magali; Dalinot, Clément; Sanguinet, Lionel; Leriche, Philippe; Roncali, Jean
Abstract: Donor-Acceptor-Donor conjugated systems are synthesized in good yield by double condensation of aromatic aldehydes of triarylamines with 2, 3-diaminomaleonitrile under microwave activation with trifluoroacetic acid as catalyst. The electronic properties of the compounds are investigated and discussed and a first evaluation of their potential as donor material in organic photovoltaic cells is presented. Graphical abstract: Highlights: Donor-Acceptor-Donor (DAD) pi-conjugated systems. Inimo chromophores obtained by basic condensation. Microwave assisted chemistry. Chromophores for organic solar cells.